Structural glaciology of Isunguata Sermia, West Greenland. Issue 2 (13th November 2018) - Jones, Christine; Ryan, Jonathan; Holt, Tom; Hubbard, Alun
ABSTRACT: We present a 1:42, 000 scale map of Isunguata Sermia, a land-terminating outlet glacier draining the western-sector of the Greenland Ice Sheet. Structure-from-Motion software applied to ∼3, 600 aerial images collected by a fixed-wing unmanned aerial vehicle in July 2015 allowed us to produce a high resolution (0.3 m ground sampling distance (GSD)) orthomosaic and digital elevation model (DEM; 1.5 m GSD).These products were used to map and describe the structural, geomorphological and hydrological features of the lower 16 km terminus of Isunguata Sermia and include many thousands of crevasses, crevasse traces and supraglacial channels. Additionally, several geomorphological features and pro-glacial hydrological features were identified, including debris-covered ice, lateral moraines and ice-marginal lakes. The map has potential for informing and reconstructing the long-term dynamic history of the glacier, including its response to variable environmental forcing.